2016
DOI: 10.1007/s12325-016-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspective of Medication Adherence in Chronic Conditions: A Qualitative Study

Abstract: IntroductionAbout 50% of patients do not take their long-term therapy for chronic conditions as prescribed. Many studies have centered on patients’ adherence to a specific treatment or single conditions, but few have taken all chronic conditions into consideration from a patient’s perspective. This study aims to explore factors that impact on drug compliance and to identify strategies to improve this from the perspective of patients with at least one chronic condition.MethodsPatients were recruited by healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 28 publications
(16 reference statements)
4
53
0
5
Order By: Relevance
“…A third of the HTxR included were unaware of the impact of non‐adherence to immunosuppression therapy and more than a half believed that their regimen was excessive. Similar results were found in other chronic conditions . However, urgent interventions are required post‐HTx, since lack of knowledge on medication increases the risk of non‐adherence, poor outcomes, and high‐economic costs …”
Section: Discussionsupporting
confidence: 76%
“…A third of the HTxR included were unaware of the impact of non‐adherence to immunosuppression therapy and more than a half believed that their regimen was excessive. Similar results were found in other chronic conditions . However, urgent interventions are required post‐HTx, since lack of knowledge on medication increases the risk of non‐adherence, poor outcomes, and high‐economic costs …”
Section: Discussionsupporting
confidence: 76%
“…To the best of our knowledge, no previous studies have formally assessed the potential impact of two modifiable aspectsthe experience of patients with healthcare and their beliefs in medicineson non-adherence to medication, with all these aspects being self-evaluated by patients without intervention from clinical teams. Previously, the impact of health beliefs and perception of disease control on medication adherence in patients with chronic disease were ascertained in a small patient-focus group study which showed that patient motivation and patient-prescriber relationships were important factors in determining medication adherence 22 . The potential to improve medication adherence by addressing the experience of patients with healthcare and their beliefs in medicines in daily clinical practice highlights the relevance of the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants attributed their nonadherence to ‘I forgot to take it' and ‘I think I am fine'. These explanations might indicate that people misunderstood their health regarding MCCs and an inability to participate in disease self‐management (Pages‐Puigdemont et al, ). Key reasons for nonadherence to treatments among MCCs population are varied, including differences in clinical variables (Kim, Bennett, Wallace, Fahey, & Cahir, ), medication beliefs (Schüz et al, ), fragmented care (Green, Hawley, & Rask, ) and synergistic effects between chronic conditions (Calderón‐Larrañaga et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…People who were not able to understand the informed consent or had difficulties complying with the research procedures were excluded. In qualitative research, data saturation is often used as a sampling principle (Morse, 2015). This meant recruitment would be stopped when no new information was found.…”
Section: Sample and Settingmentioning
confidence: 99%